An analysis of the book selection practices of Filipino parents - Calijan, Krystelle Joy A.; Santos, Yhna Therese, P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2019)
Selecting quality books for children to read does not necessarily follow a distinct standard. For a book to be the best for a child, it must reflect his own experiences and must share the same values and beliefs with him. Therefore, the role of parents in selecting books for their children is indispensable because they are the primary caregivers of the children, which makes them the most knowledgeable of their backgrounds and personalities.

However, there is relatively little information known about the criteria and influences that they consider when selecting children’s, books, especially here in the Philippines. This is why the researcher employed a descriptive research design, utilizing a structured online interview, to gather valuable insights from the Filipino parents themselves.

Thirteen parents, with children aged 2 to 11 years old, participated in the study. The respondents came from varying fields of profession, and are gathered through various means, Most of the parents claimed that they are fond of reading children’s books themselves. Factors that emerged from the study were categorized into three: content, which included genre, storyline, subject matter, and other qualities of a book that concerns the content itself; physical characteristics, which encompasses the qualities of a book that can be seen and touched, such as shape, size, design, illustrations, font style, and font size; bibliographic attributes, which pertains to the author, publisher, date of publishing, edition, and other similar details that every book has; and lastly, format, which simply refers to whether the material in in print or digital from. Another major factor that emerged is the cost and the necessity of the books.
Thesis (Bachelor of Library and Information Science)
Keywords: Book selection